Utharomyces epallocaulus Boedijn. ex Kirk & Benny. A new record from Venezuela - Delgado ívila, Adolfredo; Urdaneta García, Lilia; Piñeiro Chávez, Albino (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
On the basis of a study of coprophilous fungi from Zulia state, Venezuela, a Pilobolaceae (Mucorales) Zygomycota with simple sporangiosphores positively phototropic, arising from terminal or intercalary, subglobose, to ovoid trophocysts formed within the agar, at first erect, later decumbent, was isolated from rat and mouse dung. The sporangia is initially globose and white, and at maturity it is somewhat subglobose and black, echinulate. The subsporangial stalk has little or no pigmentation at this stage. At maturity, the wall of the subsporangial stalk is thickened and pigmented, dark brown near the sporangium but becoming paler toward the vesicle. The sporangiospores are globose to subglobose and ornamental. The specie was identified as Utharomyces epallocaulus, which represents a new record for Venezuela.